Guidelines for Strengthening the Language Teaching Training of Multigrade Teachers in Mexico - Servín Calvillo, Oscar Osvaldo (2025)
This essay contributes to the discussion on the need to incorporate the specific characteristics of multigrade schools into teacher education programs in Mexico and underscores the importance of the specialization in Spanish language teaching. To this end, an analysis of Spanish language teaching practices in multigrade primary schools is presented, with particular emphasis on the challenges observed, and recommendations are offered to strengthen both initial and continuing teacher education. The ideas presented stem from the findings of a graduate thesis conducted as part of the master’s program in Language and Mathematics Learning at the Autonomous University of Querétaro, Mexico.